1997
DOI: 10.1038/sj.ijo.0800530
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between volumes and areas from single transverse scans of intra-abdominal fat measured by magnetic resonance imaging

Abstract: OBJECTIVE:To determine the level of a single transverse scan of intra-abdominal fat between L1 and L5 vertebrae that best predicts intra-abdominal fat volumes. SUBJECTS: Sixteen male and seven female patients with non-insulin-dependent diabetes mellitus, aged 44±74 y. OUTCOME MEASURES: Volumes and areas from single scans of intra-abdominal fat measured by magnetic resonance imaging with a 1.5 Tesla magnetic ®eld strength. RESULTS: Intra-abdominal fat volumes and masses were calculated from fat areas from eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 5 publications
5
74
2
1
Order By: Relevance
“…As men frequently have more visceral fat than women, it is possible that the pattern of fat loss may be even more disparate in men than women. Further, Han et al 1 observed that intraabdominal fat areas were higher in the upper region of the L 1 -L 5 area than the lower region in men, whereas in women the intra-abodminal fat areas were similar at all levels. Taken together with the earlier studies, we conclude that MRI measurements of total abdominal fat provides a more accurate assessment of abdominal fat content and of fat loss over time than single-slice measurements.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As men frequently have more visceral fat than women, it is possible that the pattern of fat loss may be even more disparate in men than women. Further, Han et al 1 observed that intraabdominal fat areas were higher in the upper region of the L 1 -L 5 area than the lower region in men, whereas in women the intra-abodminal fat areas were similar at all levels. Taken together with the earlier studies, we conclude that MRI measurements of total abdominal fat provides a more accurate assessment of abdominal fat content and of fat loss over time than single-slice measurements.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, previous evidence has shown the assumption of a uniform VAT distribution to be incorrect. Han et al 1 demonstrated in men that intra-abdominal fat areas were higher in the upper scans in the L 1 -L 5 region than in the lower scans of this region. Lee et al 12 noted that the ranking of men for abdominal SAT and VAT deposition was dependent on the level of the abdomen at which these depots were measured.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…12,13 With the advantages of noninvasiveness and excellent soft-tissue contrast by using different imaging parameters, MRI provides a method to measure adipose tissue safely and accurately. 8,10,[14][15][16][17][18][19][20][21][22][23][24][25]27 However, measuring the fat quantity and distribution in the abdomen by MRI is generally laborious. Two steps are required to identify the volume of VAAT.…”
Section: Introductionmentioning
confidence: 99%
“…The first step is to separate fat from nonfat tissue. Thresholding on a histogram 8,[14][15][16][17]19,25 is frequently used for this task and could be accomplished automatically with good agreement between automatically and manually set thresholds. 17,19 The second step is to locate VAAT on MR image slices.…”
Section: Introductionmentioning
confidence: 99%